ANALISIS DAMPAK KEBIJAKAN UNDANG-UNDANG NOMOR 9 TAHUN 2017 TENTANG AKSES INFORMASI KEUANGAN UNTUK KEPENTINGAN PERPAJAKAN - Kumalasari, Kartika Putri; Bayani, Laras Niti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Information exchange is needed to reduce the imbalance of information or asymmetric information thatoccurs between the Directorate General of Taxes and the Bank, where the Bank has more informationneeded by the Directorate General of Taxes. However, the Directorate General of Taxes has obstacles dueto regulations that limit it in accessing taxpayer data and financial information stored in the Bank. To openaccess to taxpayer data and financial information contained in the bank, the Directorate General of Taxesmust obtain approval from Bank Indonesia through the Minister of Finance.The results of this study statethat the BRI Lampung Regional Office has not implemented and even knows of the existence of Law Number9 of 2017, but the DGT continues to disseminate information to LJK and OJK has implemented it inaccordance with POJK No. 25/POJK.03/2019. The impact that affects the Bank with the stipulation of thepolicy, as mentioned by the Directorate General of Taxes is the increase in the Bank's obligations, namelyby providing annual reports to the Directorate General of Taxes, even some Banks have to hire consultantsto study legal reporting and IT consultants, and the Bank faces issues regarding customer trust